Clinical study on acupuncture acupoints around the eyes in treating myopia in children and adolescents: A study protocol. Issue 43 (23rd October 2020) - Huang, Qun; Yang, Yang; Huang, Hui; Zheng, Yanlin; Wang, Wanjie; Liao, Tingting; Xiao, Xili; Wang, Jing; Zou, Weiwen; Wang, Juan
Abstract: Introduction: Myopia is the most common cause of avoidable visual impairment worldwide, which causes huge economic burden and social burden. There are several ways to treat and reduce myopia, but all have drawbacks; this reality drives us to search for additional effective and low-risk interventions of treatment for myopia. Acupuncture is an ancient therapy with a history of thousands of years and is now widely used in the medical system. Some randomized controlled trials have reported that acupuncture, as an adjuvant therapy, can effectively improve the diopter and vision in the sense of myopic children. Deqi is a long-standing belief to ensure the efficacy of acupuncture in the treatment of myopia, but this belief has not been confirmed by sufficient evidence of randomized controlled trials. Methods: This clinical study is a parallel-group, randomized controlled, and single blind study. Three hundred eligible adolescents will randomly be divided into acupuncture Deqi group, acupuncture without Deqi group, and waiting list group. All groups will be given frame glasses for corrective treatment; patients in the acupuncture Deqi group will be treated with acupuncture at acupoints around the eyes and flat puncture to Deqi, while acupuncture without Deqi group will not flat puncture to Deqi. The waiting list group will not receive acupuncture treatment. The primary outcome will be diopter measurement. Adverse events and safety indexes will be recorded throughout the study. Discussion: Our study will compare acupuncture Deqi with acupuncture without Deqi, and place it in a control group for the treatment of myopia. The results of this trial are expected to provide solid evidence for the effectiveness and safety of acupuncture combined with Deqi in the treatment of myopia, and hope to provide a reference for clinical practice. The primary outcome will be diopter measurement of the patients before treatment. Trial registration: ChiCTR2000037874, registered September 3, 2020.